Accuracy and Clinical Value of Maternal Incidental Findings During Noninvasive Prenatal Testing for Fetal Aneuploidies. Issue 8 (August 2017) - Brison, Nathalie; van den Bogaert, Kris; Dehaspe, Luc; van den Oever, Jessica M. E.; Janssens, Katrien; Blaumeiser, Bettina; Peeters, Hilde; van Esch, Hilde; van Buggenhout, Griet; Vogels, Annick; de Ravel, Thomy; Legius, Eric; et al.
Abstract : (Abstracted from Genet Med 2017;19(3):306–313) Genome-wide shotgun sequencing of cell-free (cf)DNA from the serum of pregnant women can identify chromosomal imbalances in an unborn fetus. Although initially developed to screen for fetal trisomies 21, 18, and 13, several studies have now demonstrated that genome-wide analysis can also detect other fetal aneuploidies, segmental imbalances, and even submicroscopic copy-number variations (CNVs).